(untitled) (Dhaka University Journal of Science, 2016)
Electrochemical studies on the interaction of Fe(III) with proton pump inhibitors (PPIs) (omeprazole, pantoprazole, esomeprazole and rabeprazole) in acetate buffer solution were carried out at gassy carbon electrode (GCE) at various pH (3.5, 4.0 and 4.5). In presence of omeprazole (Ome), the anodic and cathodic peak current for Fe(III) decreased in comparison to solely Fe(III). However, in some cases both the peaks were almost disappeared. Moreover, anodic and cathodic peaks shifted significantly towards negative potential. This is an indication that a strong interaction occurred between Fe(III) and Ome. The maximum interaction is found at 1:2 molar ratio of Fe(III) and Ome at above mentioned pH. The electrochemical interaction of Fe(III) and other PPIs was found as identical with the behavior of Ome. The electrochemical study of the interactions between metal ions and PPIs would provide important information for the technological application of PPIs in human body. Dhaka Univ. J. Sci. 64(1): 25-30, 2016 (January)